Reference gene selection for quantitative PCR in liver, skeletal muscle, and jejunum of Bos indicus cattle - Coelho,Tamara Cristina (2022)
ABSTRACT The objective of the present study was to evaluate the stability of candidate reference genes and select the genes that can be used for normalizing real-time polymerase chain reaction (PCR) in the liver, skeletal muscle, and jejunum tissues of Nellore or Nellore × Angus steers fed different diets. Fourteen purebred and 14 crossbred steers were used, in which half of the animals of each genetic group received a diet containing whole shelled corn (WSC) and the other half whole shelled corn and sugarcane bagasse (WSCB). Stability was analyzed by the RefFinder program. To validate the selection of candidate reference genes, the expression of target genes was evaluated using the different groups of reference genes. The most stable genes were 18S, ACTB, and CASC3 for skeletal muscle; HMBS, ACTB, and 18S for the liver; and GAPDH, ACTB, and CASC3 for the jejunum, regardless of breed and diet provided. Possible errors caused in data analyses were clarified comparing the more and less stable genes as reference for normalization of the target genes FASN, ACOX, SCD1, MGAM, and SLC2A1. The use of the more stable and less stable sets of reference genes may lead to different conclusions in respect to the expression profile of the target studied gene. The selection of more suitable reference genes for each experiment is of utmost importance to ensure the reliability of gene expression studies so that they can be applied in practice.